vault backup: 2025-02-16 18:42:21
This commit is contained in:
parent
5b61041480
commit
acf45de160
@ -110,7 +110,13 @@ for all $a > 0$
|
||||
|
||||
# Chain Rule
|
||||
$$ \dfrac{d}{dx} f(g(x)) = f'(g(x))*g'(x) $$
|
||||
## Examples
|
||||
> Given the function $(x^2+3)^4$, find the derivative.
|
||||
|
||||
Using the chain rule, the above function might be described as $f(g(x))$, where $f(x) = x^4$, and $g(x) = x^2 + 3)$.
|
||||
1. First find the derivative of the outside function function ($f(x) = x^4$):
|
||||
$$ \dfrac{d}{dx} (x^2 +3)^4 = 4(g(x))^3 $$
|
||||
2.
|
||||
# Trig Functions
|
||||
$$ \lim_{x \to 0} \dfrac{\sin x}{x} = 1 $$
|
||||
$$ \lim_{x \to 0} \dfrac{\cos x - 1}{x} = 0 $$
|
||||
@ -143,8 +149,8 @@ $$ \dfrac{d}{dx} \cot x = -\csc^2 x $$
|
||||
|
||||
> Differentiate $f(x) = 4\sqrt[3]{x} - \dfrac{1}{x^6}$
|
||||
|
||||
1. $f(x) = 4\sqrt[3]{x} = \dfrac{1}{x^6}$
|
||||
2. $= 4x^\frac{1}{3} - x^{-6}$
|
||||
3. $f'(x) = \dfrac{1}{3} * 4x^{-\frac{2}{3}} -(-6)(x^{-6-1})$
|
||||
4. $= 4x^{-2-\frac{2}{3}} + 6x^{-7}$
|
||||
5. $= \dfrac{4}{3\sqrt[3]{x^2}} + \dfrac{6}{x^7}$
|
||||
3. $f(x) = 4\sqrt[3]{x} = \dfrac{1}{x^6}$
|
||||
4. $= 4x^\frac{1}{3} - x^{-6}$
|
||||
5. $f'(x) = \dfrac{1}{3} * 4x^{-\frac{2}{3}} -(-6)(x^{-6-1})$
|
||||
6. $= 4x^{-2-\frac{2}{3}} + 6x^{-7}$
|
||||
7. $= \dfrac{4}{3\sqrt[3]{x^2}} + \dfrac{6}{x^7}$
|
Loading…
x
Reference in New Issue
Block a user